HIV: The deadly passenger in dendritic cells. - Rowland-Jones, S (1999)
A picture is emerging of how HIV subverts a normal immunological surveillance mechanism to establish primary infection. This involves the infection of dendritic cells at mucosal surfaces: as these cells then mature, they transport the virus to lymphoid tissue, where viral replication begins and infection of CD4(+) T cells occurs.